Engineering Design of a Voloxidizer with a Double Reactor for the Hull Separation of Spent Nuclear Fuel Rods - Young-Hwan Kim; Yung-Zun Cho; Jae-Won Lee; Ju-Hoo Lee; Sang-Chae Jeon; Do-Hee Ahn (Science and Technology of Nuclear Installations)
A voloxidizer with a double reactor capable of processing several tens of kilograms of HM/batch of nuclear spent fuel has been developed for the decladding and voloxidation of rod-cuts into hulls and pellets through the conversion of UO2 pellets to U3O8 powder. In this study, we optimized the engineering design of this voloxidizer to improve its hull-recovery ratio. First, we tested the oxidation performance of the device prototype and evaluated the effectiveness of various mechanical and chemical voloxidizing methods. On the basis of the results, we selected the screw-and-rotation method for the double rotary drum. Next, we derived a theoretical equation for calculating the optimal reactor volume for various rod-cut weights and lengths and then validated the equation using centimeter-scale acryl reactors and hulls. Subsequently, we modularized the main components such as the heater, utility, motor, reactor, valve, and structure. The double reactor was subject to preliminary separation tests of hulls and powder. Moreover, the hull-separation performance of the voloxidizer reactor was tested at a loading of 50 kg HM/batch. Finally, the remote assembling and disassembling possibility of the modules were experimentally optimized.